The influence of the spillover between futures and spot markets on hedging policy: evidence from Chinese stock markets - Shi, Kai; Gong, Junlian (Frontiers in Physics, 2023)
This paper examines the impact of risk spillovers between Chinese stock and futures markets on stock hedging policies. This paper calculates the correlation between the overall risk spillover and the hedging ratio, effectiveness, and hedging cost based on the hedging portfolio of stock futures of the CSI 300 index, the SSE 50 index, and the CSI 500 index. The results show that, on the one hand, the CSI 300 and CSI 500 futures markets are the propagators of risk spillovers, which shows that the price fluctuations of these two types of futures markets have a stronger impact on the stock spot price. The CSI 50 Futures market is the recipient of risk, and the CSI 50 Futures price is more vulnerable to the impact of the stock market. The results of the three types of samples show that when the stock market experiences extreme decline, the Risk Spillover Effect in the futures and spot markets will be significantly reduced, which indicates that the price of stocks and their derivatives is more deviated from the equilibrium relationship of pricing, and at this time, the function of derivatives in risk control is unreliable. On the other hand, the total spillover index of stock futures and spot markets has a positive correlation with hedging rate, hedging effectiveness and hedging cost. When the total spillover real number increases, it will get a more effective hedging effect. In addition, the hedging index is more sensitive to the overall spillover of high asset liquidity hedging portfolios. These conclusions provide a basis for adjusting asset positions according to the changes of Risk Spillover between the futures market and the spot market to obtain higher hedging effectiveness. The contribution of this paper is to reveal the possibility of finding the risk factors of hedging from the perspective of Risk Spillover in a very simple way, so it has reliable practicability in practice.